Immunoglobulin and complement in normal skin. Issue 12 (December 1978) - Blenkinsopp, W K; Clayton, R J; Haffenden, G P
Abstract : Cryostat sections of normal skin from 57 white adults were examined by direct and indirect immunofluorescence for immunoglobulins, complement factors, and transferrin. The results for basement membrane zone (BMX) were significantly different for the 11 face and 46 non-face biopsies: in the face, IgM was found in five, IgG in two, IgA in one, and C3 in none, whereas, in non-face, IgM was present in six, IgG in none, IgA in one, and C3 in five. The results for dermal vessel walls (DV) were not apparently different for face and non-face; in the 57 biopsies IgM was present in one, IgG in none, IgA in one, and C3 in one. The 11 biopsies from the face and 26 of the non-face biopsies were examined further. No IgD or C4 was identified, but one case (scalp) showed BMZ Clq, properdin, and transferrin, and in two cases (one face, one non-face) DV properdin was found. Cytoid bodies (IgM and IgA) were present in moderate numbers in one case; all other positive reactions were finely granular.